Do all raters value task, citizenship, and counterproductive behaviors equally: An investigation of cultural values and performance evaluations. Issue 4 (8th August 2017) - Mishra, Vipanchi; Roch, Sylvia G.
ABSTRACT: We investigated whether individualistic and collectivistic cultural values influence the extent to which raters consider task, citizenship (OCB), and counterproductive work behaviors (CWB) when evaluating overall employee performance. Participants completed a managerial role-play exercise in which they read employee performance vignettes and rated the overall performance of each employee. A relative weights approach was used to determine to what extent raters considered task, OCB, and CWB information when evaluating employee performance. Results indicated that as compared to individualistic raters, collectivistic raters placed higher weights on OCBs and less weight on task performance when assigning an overall performance rating. However, contrary to expectations, collectivistic raters did not place significantly higher weights on CWBs as compared to individualistic raters. Future research directions and practical implications are discussed.